Intracranial Lymphoma and Gradenigo Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
A 13 year old black male patient with a T-cell lymphoma who presented with Gradenigo syndrome is reported from the Department of Pediatrics, Tulane University School of Medicine, New Orleans, LA.